ChemInform Abstract: Amidato Complexes of Ruthenium, Rhodium and Iridium from Concise N—H Bond Activation: Exploration in Catalysis. Issue 42 (October 2015) - Romero, R. Martin; Fra, Laura; Lishchynskyi, Anton; Martinez, Claudio; Streuff, Jan; Muniz, Kilian
Abstract The catalysts are successfully applied in enantioselective intramolecular aza‐Michael additions as well as transferhydrogenations.